A bibliometric analysis of residents perceptions in rural tourism development using citespace - Lulu, Liu; Ramachandran, Sridar; Bidin, Sheena; Subramaniam, Thanam; Chaoyi, Cao (Taylor Francis, 2023)
Resident perception has been confirmed as a critical field in rural tourism research, and it has aroused extensive attention since the 1970s. In this study, existing publications of residents perceptions in the rural tourism field from 303 bibliographic records over two decades (2002“2021) in Web of Science are visualized through bibiliometric analysis. This study aims to analyze the existing research to identify regularities, illustrate the evolution of research content and predict research themes. As revealed by the results, (1) the number of publications in this field has increased rapidly, which could be roughly divided into three stages. (2) Most studies of residents attitudes and perception have been conducted using quantitative methods. (3) Research has progressively shifted from the beginning of residents perceptions of changes in the conservation area, to a community-based perspective, and finally to an exploration of residents satisfaction and quality of life.